Pengembangan Industri Batik Lasem Kabupaten Rembang - Tahwin, Muhammad (potensio, 2008)
Developing of small scale industry depends not only on thegovernment policies but also the industrialist, it is the ability of theindustrialist to compete their products (quality and quantity). So, theindustrialist of the small scale industry have to follow the concretesteps to endure the existence of their business. One of the small andintermediate scale industry is Batik Industry. Batik industry hasspecial characteristic, because it is the Indonesian culture whichalways exists consistency. Batik belongs to consumer’s goods. It isshopping goods that belong to heterogeneous shopping goods,because the characteristic is more important than price aspect for theconsumers. In other words, the consumers have differentperceptions about the qualities and attributes. So, developing of batikcraftsmen have to considers the relevancy between the craftsmenneeds and the program carried out.Key Words: Craftsmen, Developing.